Palatal peripheral ossifying fibroma: A rare occurrence - Agarwal, Padmanidhi (Int J Health Sci (Qassim), 2019)
Peripheral ossifying fibroma (POF) is a reactive, inflammatory, hyperplastic soft tissue growth of the gingiva. Lesions are usually labial and small with an anterior maxillary presentation, occurring commonly in the younger population. We present an unusual case of a large POF in a 68-year-old woman that presented on the posterior palate with a unique radiographic appearance. Various differential diagnoses of POF and such palatal lesions, etiopathogenesis of POF, and the surgical management of these lesions have been discussed in detail. Close post-operative follow-up of these lesions is mandatory due to the high recurrence rates.